2022
DOI: 10.1152/ajpregu.00124.2022
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian status modulates endocrine and neuroinflammatory responses to a murine mammary tumor

Abstract: Breast cancer patients have increased circulating inflammatory markers and mammary tumors increase neuroinflammation in rodent models. Menopausal status is not only important in the context of breast cancer as circulating estrogen influences tumor progression, but also because estrogen is anti-inflammatory and an essential modulator of endocrine function in the brain and body. Here, we manipulated "menopause" status (ovary-intact and ovariectomized) in an ER+ mouse mammary tumor model to determine the extent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Protein analyses of plasma determined that the potential confounding effects of CSF1R inhibition on circulating immunity were minimal in BALB/c mice (Figure S2). Indeed, PLX chow did not attenuate the previously reported tumor‐induced elevations in circulating markers 12,36,37 . Thus, the observed neuroinflammatory results were likely driven by the depletion of microglia and not a dampened peripheral‐to‐brain signal.…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…Protein analyses of plasma determined that the potential confounding effects of CSF1R inhibition on circulating immunity were minimal in BALB/c mice (Figure S2). Indeed, PLX chow did not attenuate the previously reported tumor‐induced elevations in circulating markers 12,36,37 . Thus, the observed neuroinflammatory results were likely driven by the depletion of microglia and not a dampened peripheral‐to‐brain signal.…”
Section: Resultsmentioning
confidence: 65%
“…Here, we sought to determine the extent to which microglia mediate mammary tumor‐induced neuroinflammation and behavioral side effects in a female mouse cancer model using cellular, molecular, and behavioral analyses. We have previously reported that the gene expression of cytokines and chemokines (e.g., Il1b , Cxcl1 11,12 ) is increased in the brain of this tumor‐bearing model, but the cellular source(s) of these mediators had not yet been determined. Overall, our results indicated that microglia, and likely astrocytes, contribute to mammary tumor‐induced neuroinflammation.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations